An examination of project management leadership dtyles of Nigerian quantity surveyors - A.E. Oke,; I.H. Gbadura, (Penerbit UKM, 2010)
Nigerian clients have been appointing Nigerian quantity surveyors with differs leadership styles and experience as project managers on construction projects in Nigeria over the years and this is expected to have positive or negative effect on construction works. This study examines different project management leadership styles been exhibited by Nigerian quantity surveyors using different factors as criteria. 57 questionnaires were used for the analysis out of which 15 of the respondents are quantity surveyors. Jerrell/Slevin management instrument was used in the analysis based on the identified questions on the noted 4 leadership styles and construction professionals were also involved in ranking the Nigerian quantity surveyors based on the 10 identified leadership styles using mean internal score. On the general note, Nigerian quantity surveyors were found to be autocratic using Jerrell/Slevin measuring instrument while in the opinion of Nigerian construction professionals; they are more of task oriented in discharging their duties as construction project managers. The study finally recommends democratic and transformational leadership styles for Nigerian quantity surveyors in discharging their duties as construction projects managers.